Dietary Supplements - Paul M. Coates (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
We invite you to contribute to a Special Issue of Nutrients, entitled "Dietary Supplements". The purpose of this Special Issue is to advance dietary supplement science by presenting commissioned overviews on four nutrients of particular current interest and controversy: Vitamin D, iodine, iron, and omega-3 fatty acids. To supplement these contributions, we welcome the submission of manuscripts describing original research or providing systematic reviews related to various issues in dietary supplement science. Manuscripts across a broad range of topics will be considered, but we are particularly interested in manuscripts that address the following areas: • Health effects, both positive and negative, of single nutrients, such as vitamin D, iodine, iron, and omega-3 fatty acids, with an emphasis on human studies. • Human clinical trials of dietary supplement use • Motivations for and prevalence of the use of dietary supplements • Mechanisms of action of nutrients and other bioactive components of dietary supplements. • Biomarkers of nutritional status, especially those measured in human samples. • Development and application of analytical tools for the measurement of bioactive components of dietary supplements. • Databases of dietary supplements' composition for use in improving the assessment of nutrient intake and of the exposure to ingredients present in these products in human populations.